2021
DOI: 10.21608/jppp.2021.92193.1032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gamma Irradiation on Tomato, and Pepper Growth Parameters, Phytochemical, Nematode Infectivity and detection of DNA Damage by Comet Assay

Abstract: Root -knot nematode is a challenge of most vegetable production and there is a critical need to an alternative, effective, safe technique for control. The main objective of this study was to detect the effect of five doses of gamma irradiation on Meloidogyne incognita (Mi) infectivity, host growth, and DNA damage. Three-week-old-seedlings of: tomato, (Solanum lycopersicum), and pepper (Capsicum annum), were irradiated with five doses i.e. 100, 250,500,750, and 1000 Gy and transplanted in 20cm diameter pots in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The effects of γ-radiation on the nuclear DNA of Vicia faba seeds either without treatment or treated with ZnO nanoparticles were studied using flow cytometry, an alkaline Comet assay, and the random amplification of polymorphic DNA (RAPD)-PCR; all three assays confirmed that the treatment of the seeds with ZnO nanoparticles preserved their DNA integrity [159]. Furthermore, γ-radiation is an attractive alternative to the chemicals used against an obligate endoparasite, the root-knot nematode Meloidogyne incognita that can infect most vegetables, fruits, and ornamental plants all over the world [160]. Analysis of the effects of low doses of γ-radiation on the infectivity of M. incognita, growth of tomato and pepper host plants, and DNA breakage in leaf cells using neutral Comet assays showed that the treatment of seedlings with γ-irradiation is a promising technique for nematode control without any suppressive effects on the host plants [160].…”
Section: Use Of the Comet Assay In Studies On Plants Exposed To Genot...mentioning
confidence: 89%
See 1 more Smart Citation
“…The effects of γ-radiation on the nuclear DNA of Vicia faba seeds either without treatment or treated with ZnO nanoparticles were studied using flow cytometry, an alkaline Comet assay, and the random amplification of polymorphic DNA (RAPD)-PCR; all three assays confirmed that the treatment of the seeds with ZnO nanoparticles preserved their DNA integrity [159]. Furthermore, γ-radiation is an attractive alternative to the chemicals used against an obligate endoparasite, the root-knot nematode Meloidogyne incognita that can infect most vegetables, fruits, and ornamental plants all over the world [160]. Analysis of the effects of low doses of γ-radiation on the infectivity of M. incognita, growth of tomato and pepper host plants, and DNA breakage in leaf cells using neutral Comet assays showed that the treatment of seedlings with γ-irradiation is a promising technique for nematode control without any suppressive effects on the host plants [160].…”
Section: Use Of the Comet Assay In Studies On Plants Exposed To Genot...mentioning
confidence: 89%
“…Furthermore, γ-radiation is an attractive alternative to the chemicals used against an obligate endoparasite, the root-knot nematode Meloidogyne incognita that can infect most vegetables, fruits, and ornamental plants all over the world [160]. Analysis of the effects of low doses of γ-radiation on the infectivity of M. incognita, growth of tomato and pepper host plants, and DNA breakage in leaf cells using neutral Comet assays showed that the treatment of seedlings with γ-irradiation is a promising technique for nematode control without any suppressive effects on the host plants [160].…”
Section: Use Of the Comet Assay In Studies On Plants Exposed To Genot...mentioning
confidence: 99%